Estudios que corresponden a la balística exterior - Ortiz Barrón, Cristian Adrián (Archivos de criminología, seguridad privada y criminalística, 2020)
Talking about forensic ballistics and the studies that include from its trajectory, dispersion, gravity, wind, ballistic coefficient, the projectile forms which will act giving more resistance or not to external forces, etc. Since each of them converge in the study to determine important points such as the incidence of the shot, the position where the victim was, shooter position, if the shots were inside a vehicle, that is from the inside out or from the outside to the inside, there is a lot of information that has to be collected, this in order to carry out a good criminal investigation into alleged criminal acts, some books tell us about studies in the field of external ballistics, but few they tell us what information is good or not when applying it to a specific case, the article that is developed explains the importance of external ballistics in forensic ballistics and marks the studies, as well as the information that helps to clarify the problem in relation to looking for the angles and in the victim-offender positions.